If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(j + 1) = 9 Reorder the terms: 3(1 + j) = 9 (1 * 3 + j * 3) = 9 (3 + 3j) = 9 Solving 3 + 3j = 9 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3j = 9 + -3 Combine like terms: 3 + -3 = 0 0 + 3j = 9 + -3 3j = 9 + -3 Combine like terms: 9 + -3 = 6 3j = 6 Divide each side by '3'. j = 2 Simplifying j = 2
| d+87=11(1-d)+12d+76 | | 12-7x-4-x=11-8x+2x | | 10x^2+5x+1=10 | | 10x^2+5x+5=0 | | 6/g=3 | | 10x^2+5x+1=0 | | z=0.5y*x^2 | | 2x^34=50 | | -1+9=3b-7-2b | | 6x+2x+5=2x | | cos(x+5)=sin(3x+9) | | [x-3]=2x+5 | | pq^2+pq+p^2q= | | 6x^3-9x^2-36x+8=0 | | 5y^2+40y-75=0 | | .28x=2556.36 | | 4+6=446 | | 4n-24=56 | | 5x-55=-130 | | 5n+5-7n=15-12n+10n-10 | | 0.5(4x-8)=6x+10 | | 3G+24=9f | | -8x^2+12x+2=4x | | (x+1)(x+2)(x-2)=x^3+8 | | t*3-4=15 | | 9xy/7= | | -58+5y+4=3(4y-3)-3 | | 7m-22=32 | | 3/(w-3)-3/5=w/(w-3) | | 4x+5x=2 | | y^-2=4/16 | | x^2+2x^2=80 |